Small and medium scale enterprises and economic growth in Nigeria - Ibitomi, Taiwo; Dada, Durotimi Amos; Ayedogbon, Joseph Olanipekun; Micah, Ezekiel Elton Mike; Aderotimi, Bankole (Journal of Social Sciences and Management Studies, 2024)
Due to the inconclusive situation of empirical studies on Small and Medium Enterprises ( SMEs)  and economic growth in Nigeria and the need to promote growth accompanied by poverty alleviation, this study examined SMEs financing and economic growth in Nigeria from 1999 to 2021. The hypotheses formulated and tested in the study included that there is no significant relationship between commercial bank loans, total credit to the private sector (which captures other means of financing SMEs) and lending rate. Annual data was collected from the Central Bank Statistical Bulletin. The augmented Dickey-Fuller unit root test revealed that the variables were stationary at the first difference, while the Johansen co-integration test indicated a long-run relationship among the variables. The Vector Error Correction Mechanism (VECM) indicated commercial bank loans have a weak negative effect on economic growth. Total credit to the private sector has a positive effect on economic growth, while lending rates have a significant negative effect on economic growth. It was concluded that SMEs financing has significant positive effects on economic growth in Nigeria. It was recommended that the government encourage more commercial bank loans to SMEs by guaranteeing such loans, more development bank branches should be established; and the lending rate should be lowered.